A Stydy : Multi-dimensional elements of development of a district (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Globalization has led to rising issues approximately the development of arias; its miles envisaged that whilst the advanced areas will continue to grow similarly, the underdeveloped or backward regions would possibly similarly get marginalized. For maintaining average development, there is a need for a well-balanced improvement. For the motive, it is important to expand region-specific improvement strategies which can be framed on the idea of local context. Which include assets? In India, with lifestyles of many backward regions, there is a want to identify the extent of backwardness and its volume so one can expand effective strategies for the improvement of the area. The present day observes examines the level and typology of improvement in Churu district of Rajasthan. The Rajasthan location lies within the semi-arid area and is majorly inhabited through Moe Muslims. Water 1s scarce within the place, and therefore, rain is still the important supply of irrigation. Despite harsh climatic conditions Agriculture is the predominant livelihood option. Furthermore, because of cultural practices, farmers in Rajasthan